Optimize Production Based on Goods Using Supply Chain Management - Retnowo, Murti; Waluyo, Anita Fira (Institut Teknologi Dirgantara Adisutjipto, 2019)
Competitive competition and the advent of the global marketplace becomes its own challenges, these challenges are associated with getting products and services are timely and low cost. Resolution to face both these things one of which with the application of Supply Chain Management (SCM). SCM is very effective for use in addressing the supply chain and securing competitive advantage and improve organizational performance not only within the Organization but the Organization among the supply chain. SCM will be used to provide the information the State of the stocks of raw materials and will be enabled as a reminder (reminder) and the order of the raw materials to the supplier by using Massage Passing or SMS Gateway. Model SCM is expected to control the inventory of goods, either over stock or stocks that are already able to save stock with time quickly and efficiently.